Indium-mediated C-allylation of melibiose - Denner, Christian; Gintner, Manuel; Kählig, Hanspeter; Schmid, Walther (Beilstein Journal of Organic Chemistry, 2019)
The indium-mediated allylation reaction has been applied to melibiose, a disaccharidic substrate. This elongation methodology allows for a short, efficient and diastereoselective approach towards complex glycosylated carbohydrate structures. The stereochemical outcome of the key intermediates, allylated disaccharides, has been determined by X-ray analysis. Ozonolysis of the introduced double bond yielded the unprotected elongated disaccharides in the equilibrium of the pyranoid as well as furanoid isomers in both anomeric forms, respectively. Per-O-acetylation has been performed to facilitate separation of the isomeric mixture for structural identification. The main product revealed to adopt a β-pyranoid form of the elongated unit at the reducing end of the disaccharide.
Keywords: carbohydrates; C–C bond formation; indium-mediated allylation; melibiose; ozonolysis

(untitled) - Kozikowski, A. P.; Sorgi, K. L.; Wang, B. C.; Xu, Z.-b. (Tetrahedron Lett., 1983)

(untitled) - Schmid, W.; Whitesides, G. M. (J. Am. Chem. Soc., 1991)

(untitled) - Li, C. J.; Chan, T. H. (Tetrahedron Lett., 1991)

(untitled) - Chan, T. H.; Li, C. J. (J. Chem. Soc., Chem. Commun., 1992)

(untitled) - Chan, T. H.; Isaac, M. B. (Pure Appl. Chem., 1996)

(untitled) - Paquette, L. A.; Mitzel, T. M. (Tetrahedron Lett., 1995)

(untitled) - Bernardelli, P.; Paquette, L. A. (J. Org. Chem., 1997)

(untitled) - Fischer, M.; Schmölzer, C.; Nowikow, C.; Schmid, W. (Eur. J. Org. Chem., 2011)

(untitled) - Balla, E.; Zamyatina, A.; Hofinger, A.; Kosma, P. (Carbohydr. Res., 2007)

(untitled) - Schmölzer, C.; Fischer, M.; Schmid, W. (Eur. J. Org. Chem., 2010)

(untitled) - Prenner, R. H.; Schmid, W. (Monatsh. Chem., 1996)

(untitled) - Gordon, D. M.; Whitesides, G. M. (J. Org. Chem., 1993)

(untitled) - Gintner, M.; Yoneda, Y.; Schmölzer, C.; Denner, C.; Kählig, H.; Schmid, W. (Carbohydr. Res., 2019)

(untitled) - Prenner, R. H.; Binder, W. H.; Schmid, W. (Liebigs Ann. Chem., 1994)

(untitled) - Kim, E.; Gordon, D. M.; Schmid, W.; Whitesides, G. M. (J. Org. Chem., 1993)

(untitled) - Albler, C.; Hollaus, R.; Kählig, H.; Schmid, W. (Beilstein J. Org. Chem., 2014)

(untitled) - Binder, W. H.; Prenner, R. H.; Schmid, W. (Tetrahedron, 1994)

(untitled) - Gintner, M.; Denner, C.; Schmölzer, C.; Fischer, M.; Frühauf, P.; Kählig, H.; Schmid, W. (Monatsh. Chem., 2019)